Levels of circulating catestatin in different clinical variants of coronary heart disease in patients with chronic heart failure and concomitant type 2 diabetes mellitus and obesity - K. M. Borovyk; O. I. Kadykova; P. H. Kravchun (Patologìâ)
The aim is to assess the levels of circulating catestatin and to establish relationships with various clinical variants of coronary heart disease (CHD) in patients with chronic heart failure (CHF) and concomitant type 2 diabetes mellitus (T2DM) and obesity.